Nanocarriers: Novel Approaches to Oral Delivery of Insulin - KERİMOĞLU, OYA; ÖZER ÖNDER, SETENAY; UĞURLU, TİMUÇİN (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Diabetes is among the major chronic diseases at present, and no medication has been developed that can replace the roles of endogenous insulin, especially for type 1 diabetes patients. However, insulin can be frequently administered by the subcutaneous route as a protein macromolecule because enzymatic and absorption-associated problems. It leads to immunogenic symptoms, adipose tissue complaints such as lipodystrophy, and hyperinsulinemia risks because of pharmacokinetic properties that do exactly overlap with those of endogenous insulin. In a remarkable number of patients, failure to attain permanent glycemic control by subcutaneous insulin treatment has shown by clinical trials based on noncompliance. Oral drug administration has always been the most preferred administration pathway for drugs with high patient compliance and convenience. Difficulties in the use of subcutaneous insulin have prompted scientists to find solutions for the oral administration of insulin. Similar to many other fields, nanotechnology has recently come to the fore in the pharmaceutical field. Compared with conventional systems, nanopharmaceuticals are drug delivery systems that enable promoted absorption, protection of the active ingredient from the external environment, lower dose applications, higher bioavailability, controlled release, and prolonged residence time. In vitro and in vivo studies have been performed with varied nanopharmaceutical systems in order to administer insulin orally for this purpose.
Keywords: Nanosystems; insulin; oral delivery; diabetes; bioavailability; oral peptides; DRUG-DELIVERY; IN-VIVO; SYSTEM SNEDDS; PARTICLE-SIZE; NANOPARTICLES; PEPTIDE; VITRO; ABSORPTION; LIPOSOMES; NANOGELS